Projeto de um nó LoRaWAN híbrido com repetidor embutido de baixo custo e baixo consumo de energia - Maziero, Lucas (2021)
The Internet of Things (IoT) is a theme that has grown a lot, with this the LPWAN (Low Power Wide Area Network) has gained space in the telecommunications market. In this market related to IoT, the LoRa technology has been standing out, precisely because it has the desired characteristics of an IoT device which is, wireless communication over long distances with low power consumption, which enables the use of batteries for a long period. The LoRaWAN protocol was designed for the Internet of Things, using LoRa modulation as a physical means of communication and providing network security, since the data that travel there are encrypted. This work proposes the development of a Hybrid LoRaWAN Node that includes a Basic LoRaWAN Node and a LoRaWAN Repeater embedded in the same device, thus, besides working as a classic LoRaWAN device with LoRaWAN packet repeater capability in a totally transparent way in the LoRaWAN network. The results show that adding the Hybrid LoRaWAN Node to the LoRaWAN network significantly increases the packet delivery rate, as well as increasing coverage, mitigating costs and increasing the reliability of the LoRaWAN network.